CHARACTERISTICS OF THIOL-DISULFIDE SYSTEM AND NITROSATIVE STRESS IN NEURONS IN CONDITIONS OF GLUTAMATE EXCITOTOXICITY MODELING IN VITRO AS THE RESULT OF APPLICATION OF NOS INHIBITORS OF VARIOUS SELECTIVITY - Горбачова С. В.,; Беленічев І. Ф., (World of Medicine and Biology, 2015)
The given experimental investigation is dedicated to the studying of non-selective inhibitor efficiency of constitutional NO-synthase isoforms - N-nitro-L-arginine methyl ester (L-NAME) and selective inhibitor of neuronal NO-synthase - N-Propyl-L-arginine. The work is performed using allocated neuronal suspension. Besides investigated medicines there has been added a glutamate in neurotoxic concentration (100 mcmoles) into this suspension. An increased level of nitrite by 51,8% in the 30-minute observation, by the end of the observation of the level higher than the initial value of 2,6 times. Similar results were obtained for the level of nitrotyrosine, the concentration of which 52,3% was higher than the baseline at 60 minutes of observation. In parallel with the formation of nitrosative stress observed malfunction of the antioxidant system, which was manifested in the accumulation of free radicals, and as a consequence, increase in the level of oxidative modification of protein molecules. Elevated levels of aldehyde and ketone derivatives of proteins was recorded at 30 minutes - by 20,4% and 22,9% respectively. Oxidative modifications in these conditions amenable and cellular enzymes. We have a 60-minute observation, a decrease by 37,3% of the activity of SOD, which plays a key role in the removal of the formed superoxide radicals accumulate in the tissues in large quantities.Adding to the incubation medium of N-propyl-L-arginine caused a significant decrease manifestations nitrosative stress and its effect was more lasting. This compound is also active at the 30 minute observation, as indicated by reduction in NO 21,5%; nitrotyrosine – 22,2%; APH – 35,9%; KPH – 57,1%. The content of oxidized glutathione in this experimental series was reduced by 16,7%. At later stages of observation in this series had elevated levels of markers of nitrosative and oxidative stress, however, the values obtained were lower than in series with the addition of N-nitro-L-arginine, which indicates a more prolonged effect of N-propyl-L-arginine against studied parameters.Analysis of the results showed a presence of ill-defined effect correspondingly to the limitation of NO-dependent mechanisms of neurodestruction among both using compounds which was exhibited only on the initial stages of glutamate excitotoxicity. Statistically significant differences have been observed only concerning nitrotyrosine level, stable metabolites of nitric oxide and markers of oxidized modification of protein molecules. N-Propyl-L-arginine was a leader by such characteristics as intensity and duration. The obtained data showed a limited value of neuronal isoform of NO-synthase in conditions of glutamate excitotoxicity. In the given conditions more essential role in pathobiochemical reactions belongs to an inducible isoenzyme which inhibitors are advisable to apply during the recovery period of cerebral ischemia.
Keywords: NO-synthase inhibitors; thiol-disulfide system; nitrosative stress; glutamate excitotoxicity